Understanding of Punishment in the Philosophical, Political and Legal Doctrines of Ancient China (Law and Safety, 2019)
Based on the analysis of the philosophical, political and legal doctrines of Ancient China – Taoism, Confucianism, Mo-tze’s guidelines, Mo-dze’s teachings, Legist and Orthodox Confucianism – the authors have demonstrated specific features of understanding the essence of punishment in the ancient Chinese society. The factors that influenced the establishment and development of the institution of punishment in China have been revealed. It has been noted that the specificity of the criminal legislation of the Ancient China was the fact that the reality of the threat to the current government was foremost taken into account while determining the punishment. The most dangerous were considered acts that threatened the ruler, less dangerous that threatened society. Therefore, all punishments can be divided into those that threatened the authority of government, and those that did not directly affect the interests of the ruler. The basic principles of implementing punishments have been defined.The authors have concluded that the philosophical teachings of Ancient China had significant differences from many political issues, but were similar in understanding the role and purpose of punishment. For the most part, the use of punishment was united into a single system with rewards, which had one purpose: to centralize and strengthen the ruler’s power, to liquidate his political opponents, and to curb the disobedience of the people in all its manifestations. Consequently, punishment was considered as one of the methods of managing a society. It has been noted that there was no understanding about the law in the ancient world. Punishment did not become a separate institution. There was a gradual formation of the institution of punishment. Religion and the morale of those times greatly influenced on that process.
Keywords: Ancient China; punishment; institution of punishment; understanding of punishment; principles of applying the punishment; philosophical doctrines